A framework for data-driven informatization of the construction company. (January 2019) - You, Zhijia; Wu, Chen
Abstract: With the advent of big data era, the construction industry has focused on processing large quantities of engineering data and extracting their value. However, inaccurate manual entries and delayed data collection have created difficulties in making full use of information. Meanwhile, difficulty sharing data and weak interoperability of data among business information systems also leaves company headquarters without the resource integration that can facilitate decision making. To overcome these challenges, we proposed a big data infrastructure called the enterprise integrated data platform (EIDP) for use by construction companies. We discuss a case study, and offer a framework for future business improvement that contributes to closed-loop construction supply chain management, cost management and control, knowledge discovery, and decision making. The proposed informatization solution provides a theoretical basis for realizing data sharing and interoperability between business management and project management. On this basis, it will help construction companies to improve the efficiency of both company operations and project delivery by optimizing the business process and supporting decision making.